Imagining Science Education Through Ethnographies of Neoliberal Resistance. (2nd July 2016) - Weinstein, Matthew
ABSTRACT: This article describes translation of research on resistance against neoliberalism into the curriculum of a science teacher certification program. It examines the way that the discourse of STEM reorganizes science as a neoliberal project. It summarizes the author's ethnographic work on street medicine, i.e., the medical practices developed to support patients in states of emergency and, centrally, protesters at counter neoliberal/corporate globalization protests as a technoscientific counter-neoliberal practice. Finally, it describes how this analysis of STEM and ethnographic work informs our teacher education work, resulting in a program we call STEAMD: Science, Technology, Engineering, Arts, Math, and Democracy.